DC Current Measurement Using Magnetic Flux in an Electronic Null Balancing Arrangement - Escoto, Jr., Miguel T. (Philippine Engineering Journal; Vol 26 No 1 (2005), 2011)
DC current measurement using magnetic flux balancing with an automatic controller is presented. A ferromagnetic, toroidal core is used both as a flux detector and magneto motive force summer element. A symmetrical, AC triangular current sent through an excitation coil builds up flux in the core. The DC current to be measured is sent through a another coil, which sets up a bias magneto motive force or mmf. The bias mmf causes the core to reach saturation earlier on one side of the flux build up than on the other side. As core saturation is reached, a voltage pulse transition is detected in a separate winding by a Schmitt trigger. Its duty cycle varies with the amount of flux imbalance affecting an automatic control feedback which strives for zero flux, by sending an opposing current, through a fourth coil, producing a canceling flux. An electronic null balancing circuit was wired to verify the technique. Keywords: Coercion point, flux, magneto motive force, Opamp, proportional-integral, residual flux, remanence, saturation, Schmitt trigger